Four-week remotely supervised aerobic exercise during the COVID-19 era: Exploring physical performance and psychosocial health in adults without COVID-19 living in rural settings - Bayrak, Gokhan; Aslan, Ummuhan Bas (Lippincott Williams & Wilkins, 2025)
Rationale:Aggressive osteoblastoma (AO) is an extremely rare cancer that mainly affects the spine and long bones and is less frequent in craniofacial bones. Cases involving the skull are even rarer, and the low incidence rates limit our understanding of the distribution and treatment strategies of AO. The aim of this study was to explore the clinical features, imaging findings, pathological characteristics, diagnoses, treatment, and prognosis of AO involving the skull.Patient concerns:A 13-year-old male was admitted to the hospital with a painless mass on the forehead that had gradually enlarged over the past year.Diagnoses:Magnetic resonance imaging of the head revealed an abnormal signal corresponding to a region with an unclear boundary measuring 2.32 cm x 2.23 cm x 2.64 cm on the left side of the frontal bone.Interventions:The entire mass was removed, and postoperative pathological examination led to a diagnosis of epithelioid osteoblastoma.Outcomes:The patient was periodically followed up for a year, and no tumor recurrence or metastasis was observed.Lessons:AO can be diagnosed on the basis of histological examination, immunohistochemical analysis, and imaging. Gross tumor resection and regular re-examination are suitable treatment options.Level of evidence:Level I - randomized-controlled study.
Keywords: aerobic exercise; anxiety; COVID-19; physical activity; quality of life